2012
DOI: 10.1094/pdis-09-11-0793
|View full text |Cite
|
Sign up to set email alerts
|

Races of Puccinia graminis f. sp. tritici with Combined Virulence to Sr13 and Sr9e in a Field Stem Rust Screening Nursery in Ethiopia

Abstract: North American durum lines, selected for resistance to TTKSK (Ug99) and related races of Puccinia graminis f. sp. tritici in Kenya, became susceptible in Debre Zeit, Ethiopia, suggesting the presence of stem rust races that were virulent to the TTKSK-effective genes in durum. The objective of this study was to characterize races of P. graminis f. sp. tritici present in the Debre Zeit, Ethiopia stem rust nursery. Three races of P. graminis f. sp. tritici were identified from 34 isolates: JRCQC, TRTTF, and TTKSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 16 publications
3
107
2
Order By: Relevance
“…This is of concern as these two genes are sources of stem rust resistance in the majority of durum cultivar in North America. Olivera et al (2012) screened 338 accessions of emmer wheat and, based on seedling as well as APR screening at Debre Zeit, Ethiopia, confirmed that 11 genotypes were useful in breeding.…”
Section: Status Of Existing Prevalent Racesmentioning
confidence: 85%
See 3 more Smart Citations
“…This is of concern as these two genes are sources of stem rust resistance in the majority of durum cultivar in North America. Olivera et al (2012) screened 338 accessions of emmer wheat and, based on seedling as well as APR screening at Debre Zeit, Ethiopia, confirmed that 11 genotypes were useful in breeding.…”
Section: Status Of Existing Prevalent Racesmentioning
confidence: 85%
“…Olivera et al. () screened 338 accessions of emmer wheat and, based on seedling as well as APR screening at Debre Zeit, Ethiopia, confirmed that 11 genotypes were useful in breeding.…”
Section: Status Of Existing Prevalent Racesmentioning
confidence: 95%
See 2 more Smart Citations
“…Genes Sr9e and Sr13 constitute major components of resistance in North American durum cultivars (Olivera et al. ), and Sr9e and Sr12 are common in CIMMYT‐derived durum lines (Singh et al. ).…”
Section: Discussionmentioning
confidence: 99%